Analisis Kelayakan Pembukaan Toko Tas Esgotado Ditinjau Dari Aspek Pasar, Aspek Teknis, Dan Aspek Finansial - Suryo Azdkiyo Abe Abe; Budi Praptono; Maria Dellarosawati (eProceedings of Engineering, 2016)
Esgotado small and medium-scale company that stood since November 2012. Esgotado located in the city of Bandung, at this location Esgotado produce and sell their products online. During this time Esgotado been doing promotions through social media such as websites, twitter & facebook that keep running until ini.Since information technology is growing rapidly and proved to be very supportive and helpful to the process of marketing and selling products, but with the number of shopping destinations in the cities greater then the conventional sales process through transactions on shopping remains an important issue in improving product sales. with many opportunities that can be optimized by the company Esgotado that one of the huge market potential of the region, the city of Bandung as one of the opportunities that can be exploited by management Esgotado to improve profoit. Companies Esgotado want to increase sales revenue by opening stores ofline to market its products, the need to store opens investment feasibility analysis Esgotado bag In this study, the financial aspect is calculated in the form of investment funds, expected revenues, operating costs, state revenue, cash flow and balance sheet to assess the level of investment as PBP, NPV, IRR. Periods in making financial projections is set for 5-year financial projections by MARR = 14%. The result of the calculation of the level of investment that is: NPV = Rp. 225,922,772 IRR = 59% and PBP = 1.50 years. ofline store openings feasible or greater than MARR IRR and NPV positive. Keywords: Feasibility Analysis , NPV , IRR , PBP , Esgotado Ofline Store